How is the Development of Integrated Marketing Communication (IMC) Research on MSMEs in Indonesia from 2017 to 2023: A Bibliometric Analysis Approach - Muttaqien, Zaenul; Sudarmiatin, Sudarmiatin; Munawaroh, Nuril Aulia (Formosa Journal of Science and Technology, 2024)
This study employed secondary data extracted from scholarly articles in both Indonesian and English sourced through Google Scholar. Utilizing the Publish or Perish software, the inquiry centered on the keywords "Integrated Marketing Communication" and "MSME" without initially setting a specific time frame. The preliminary search returned 125 papers spanning from 2009 to 2024. Following this, refinement criteria were applied, leading to the identification of 53 articles meeting the predefined criteria for inclusion in the analysis. Subsequently, Zotero software was utilized to augment the metadata of these articles, encompassing author names, titles, publication journals, and abstracts. The dataset underwent descriptive statistical analysis to delineate the number of publications, research methodologies, publication types spanning from 2017 to 2023, alongside the top 10 articles based on citation count.